Pengaruh Perceived Risk, Ease of Use, dan Comfortability terhadap Minat Penggunaan Sistem Pembayaran Digital e-money (Studi Kasus Transjakarta) - Akbar Imam Muzaki; Gatot Nazir Ahmad; Diena Noviarini (INDO PUBLISHING, 2025)
This study aims to determine the effect of Perceived Risk, Ease of Use, and Comfortability on the Intention to Use E-Money, both partially and simultaneously. This is a quantitative research study. The population consists of students from the Faculty of Economics at Universitas Negeri Jakarta, aged 17–50 years, with a sample size of 120 respondents. The sampling technique used was purposive sampling, and data collection was carried out using questionnaires. The results show that: (1) Perceived Risk has a negative and significant effect on the Intention to Use E-Money, with a t-value (6.608) > t-table (1.981) and a significance level of 0.000 < 0.05; (2) Ease of Use has a positive and significant effect on the Intention to Use E-Money, with a t-value (3.979) > t-table (1.981) and a significance level of 0.000 < 0.05; (3) Comfortability has a positive and significant effect on the Intention to Use E-Money, with a t-value (5.585) > t-table (1.981) and a significance level of 0.000 < 0.05; and (4) Perceived Risk, Ease of Use, and Comfortability simultaneously have a significant effect on the Intention to Use E-Money, with an F-value (121.133) > F-table (2.69) and a significance level of 0.000 < 0.05. The coefficient of determination (R²) is 0.773, indicating that 77.3% of the variation in the intention to use e-money can be explained by the three independent variables in this model.